2014
DOI: 10.1074/jbc.m114.586024
|View full text |Cite
|
Sign up to set email alerts
|

Glutathionylation of the Aquaporin-2 Water Channel

Abstract: Background:The trafficking of the vasopressin-dependent water channel AQP2 is regulated by post-translational modifications as phosphorylations and ubiquitylation. Results: AQP2 is subjected to S-glutathionylation, which is modulated by ROS production. Conclusion: AQP2 is sensitive to oxidative stress. Significance: Identifying this novel post-translational modification is crucial to understand renal diseases characterized by oxidative stress and AQP2-dependent water balance disturbance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…However, preliminary in silico analysis using NetOGlyc [ 33 ] and NetPhos [ 34 ] revealed the presence of several putative glycosylation and phosphorylation sites on RmAQP2 (data not shown). Post-translational modifications of AQP have been previously described [ 35 37 ] and it may be one explanation for the detection of larger protein products in the immunoblot assays. Structural predictions suggest that this protein may exist in the membrane as a tetramer and the multiple banding pattern in the blot could represent varying stages of the breakdown of this tetrameric structure; cleavage of the intracellular tails of the RmAQP2 would result in a molecular mass of ≈ 25 KDa, suggesting that the larger 50 KDa band could be a dimer of two molecules.…”
Section: Discussionmentioning
confidence: 99%
“…However, preliminary in silico analysis using NetOGlyc [ 33 ] and NetPhos [ 34 ] revealed the presence of several putative glycosylation and phosphorylation sites on RmAQP2 (data not shown). Post-translational modifications of AQP have been previously described [ 35 37 ] and it may be one explanation for the detection of larger protein products in the immunoblot assays. Structural predictions suggest that this protein may exist in the membrane as a tetramer and the multiple banding pattern in the blot could represent varying stages of the breakdown of this tetrameric structure; cleavage of the intracellular tails of the RmAQP2 would result in a molecular mass of ≈ 25 KDa, suggesting that the larger 50 KDa band could be a dimer of two molecules.…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that the increase in AQP2 glutathionylation is paralleled by higher ROS production. Conversely, low levels of ROS, measured in cells displaying low intracellular calcium concentration, secondary to the expression of the calcium-sensing receptor (CaSR), associates with reduced S-glutathionylation of AQP2 [ 130 ]. Whether or not S-glutathionylation of AQP2 is involved in the water imbalance observed during aging remains to be investigated.…”
Section: Role Of Vasopressin/aqp2 Axis and Oxidative Stress In Agimentioning
confidence: 99%
“…This effect was blunted by phosphodiesterases inhibitors, suggesting that O 2 − enhances cAMP degradation [ 99 ]. In addition, exposure of mice kidney slices to tert-butyl hydroperoxide increases AQP2 glutathionylation [ 100 ]. Taken together these data indicate that O 2 − and H 2 O 2 participate in the regulation of AQP2, but fundamental measurements of water permeability are missing.…”
Section: Collecting Ductsmentioning
confidence: 99%